Analysis of Human Errors Related to Many Marine Accidents Occurring While Anchoring and Manoeuvring at an Anchorage - Grzegorz Rutkowski (Scientific Journal of Gdynia Maritime University, 2019)
The purpose and scope of this paper is to describe anchoring procedures and typical human errors that are the cause of many marine accidents related to the anchoring of vessels and their manoeuvring in anchorage areas. In this paper the author focuses on typical marine accidents recorded for very large crude carriers (VLCC). As a result of the analyses, it can be seen that in the vast majority of cases these accidents are caused by human error and are related to the violation of accepted maritime anchor practices and a failure to observe the relevant safety and security procedures. The consequences of the accidents vary from the minor (e.g. slight structural damage to the anchor winches or other marine equipment) to the serious, which result in dry dock repairs due to hull damage, loss of stability and/or loss of navigability. The described cases refer to both favourable and extremely unfavourable hydro meteorological conditions, the latter including strong winds, currents and waves within the confined anchorage area.